Beyond post‐politics: Offsetting, depoliticisation, and contestation in a community struggle against executive housing. Issue 2 (23rd November 2019) - Apostolopoulou, Elia
Abstract : In this paper I seek to explore the role of biodiversity offsetting in the evolution of public debates over controversial urban development projects and the way it may influence the outcome of social‐environmental conflicts. By drawing on empirical data obtained through 25 interviews with key stakeholders involved in a conflict around executive housing in North East England, 48 interviews with several stakeholders involved in offsetting across England, and an extensive document analysis, I explore the depoliticising effects of offsetting as an indicative example of actually existing neoliberal conservation. I also pay attention to the way offsetting relates to the fast policy complex to trace the links between neoliberalisation and depoliticisation particularly in the era following the 2008 financial crash. Understanding social‐environmental conflicts through the lens of the post‐political hypothesis can shed light on the way both participatory planning and neoliberal conservation, by favouring technocratic management and consensual policy‐making, attempt to remove contestation and agonistic engagement from the public terrain. On the other hand, seeing conflicts only through the post‐political hypothesis has important limits, primarily because it implies a catholic hegemony of post‐politics that can be both disorienting and paralysing. I conclude by showing through five key propositions the necessity for contextualised readings of historically and geographically specific political practices and for analysing depoliticisation by means of a theory of hegemony. Abstract : In this paper I seek to explore the role of biodiversity offsetting in the evolution of public debates over controversial urban development projects and the way it may influence the outcome of social‐environmental conflicts. By focusing on a conflict around executive housing in North East England, I explore the depoliticising effects of offsetting, as an indicative example of actually existing neoliberal conservation. I conclude by showing through five key propositions the necessity for contextualised readings of historically and geographically specific political practices and for analysing depoliticisation by means of a theory of hegemony.